Congenital diaphragmatic hernia: prevalence and management - Gatea, Hasan K.; Al-Gailani, Faik T.; Abulhab, Raghad J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: The morbidity and mortality of congenital diaphragmatic hernia is related to the severity of lung hypoplasia ,pulmonary hypertension and associated anomalies.Patients and methods: fifty nine consecutive patients with surgically proved diaphragmatic hernia (excluding hiatal hernia) were included in this prospective study. All patients were seen at Al- Kadhymia hospital for children and Al-Mustansyria hospital, in the period from January 2003 to December 2009.Plain chest x-ray was done for all the patients understudy, but barium study was arranged for only nine patients.Results: There were fifty nine child with congenital diaphragmatic hernia , Bochdalek hernia forms 81.4% of all congenital diaphragmatic hernia, the peak incidence at presentation was in the neonatal period (80,2%) of patients. The chest roentgenographic appearance was diagnostic in 87.5% of the patients with Bochdalek while Morgagni hernia in 62.5% of patients was diagnostic. Morgagni hernia constitutes 13.6% of the congenital variety, commonly to the right side (87.5% of patients ).The incidence of presentation beyond the neonatal period was 50% of cases . Absence of hemidiaphragm was found in 5% of the congenital variety , the chest x-ray was diagnostic in all patients.Conclusion: The chest roentgenograph (frontal view) is a very helpful diagnostic tool for the diaphragmatic hernia with a high diagnostic accuracy (73.7%).